People's Republic of China : 2018 Article IV Consultation-Press Release; Staff Report; Staff Statement and Statement by the Executive Director for the People's Republic of China. (IMF Staff Country Reports; Country Report ;, 2018)
China is at an historic juncture. After decades of high-speed growth, the authorities are now focusing on high-quality growth. Whether and how this shift is carried through will determine China's development path for decades to come. Recent strong growth momentum and significant financial de-risking progress reduce the probability of a near-term abrupt adjustment. Rebalancing accelerated in some dimensions, especially as the current account surplus continued to fall and growth became less dependent on credit, but progress slowed in many other dimensions as exports drove the growth pick up, rather than consumption. And while credit growth has slowed, it remains excessive.